The development of a scenario-based human-machine-environment-procedure (HMEP) classification scheme for the root cause analysis of helicopter accidents. (September 2022) - Chi, Chia-Fen; Sigmund, Davin; Lin, Yu-Chieh; Drury, Colin G.
Abstract: The current study analyzed the root causes of 22 helicopter accidents/incidents that took place between 1998 and 2019. Each root cause was coded using three commonly used classification models in aviation HFACS, ATSB, and IATA to identify recurring factors for better targeting of future prevention strategies. The frequency analysis revealed that not following procedure (22 observations), training inadequate or unavailable (17), inadequate regulatory oversight (17), inadequate procedure guidance (16), company management absent or deficient (10) and incorrect manuals/charts/checklists (9) were the most frequent contributing factors. Since none of the existing models could summarize the root causes of 22 occurrences effectively, a scenario-based human-machine-environment-procedure (HMEP) classification scheme was proposed to use organizational influences, people management, technical failure, procedure and document, and environment as the first-layer subcategories. The HMEP scheme was additionally applied to the analysis and coding of 4 helicopter accidents in the USA published by the NTSB. The HMEP scheme revealed that NTSB had identified a significantly greater number of root causes in the manufacturer design, manufacturing & documentation. Overall, HMEP can be used to guide the data collection during accident investigation and subsequently to aggregate aviation accidents to derive recurring factors and compare accident patterns in an efficient manner. Highlights: Develop a scenario-based classification schemes for the root cause analysis of helicopter accidents. Use organizational influences, people management, technical failure, procedure and document, and environment as the subcategories. Derive recurring factors and compare accident patterns of helicopter accidents/incidents.